1994
DOI: 10.1152/jappl.1994.77.4.1617
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency function: improvement of classical bioheat approach

Abstract: In view of the complex vascular architecture and the intricate physical heat transfer processes in the human body, convective heat transfer via the blood is generally described by simple substitutional processes ("non-vascular models"). The classical "bioheat" approach of Pennes (J. Appl. Physiol. 1: 93-122, 1948), defining the heat flow to or from the tissue as being proportional to the product of perfusion rate and the difference of arterial and tissue temperature, has been seriously questioned after having … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…For skin a correction of perfusion term is not necessary [Brinck and Werner, 1994;Weinbaum et al, 1997]. Our data shows that the BHTE accurately predicts local hyperthermia only at low blood perfusion rates.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…For skin a correction of perfusion term is not necessary [Brinck and Werner, 1994;Weinbaum et al, 1997]. Our data shows that the BHTE accurately predicts local hyperthermia only at low blood perfusion rates.…”
Section: Discussionmentioning
confidence: 84%
“…Applying different thermal models for prediction of heat transfer in perfused tissue, many authors suggested that the BHTE is valid for describing mean temperatures and hyperthermia in peripheral tissue such as an inner cutaneous layer [Dagan et al, 1986;Song et al, 1987Song et al, , 1988Baish, 1994;Brinck and Werner, 1994]. For skin a correction of perfusion term is not necessary [Brinck and Werner, 1994;Weinbaum et al, 1997].…”
Section: Discussionmentioning
confidence: 99%
“…The fi rst limitation is that it considers that all the heat leaving the artery is absorbed by the local tissue and there is no venous rewarming. 132 Brinck and Werner 133 and Wissler 134 suggested a correction coeffi cient that is less than unity and accounts for venous rewarming that should multiply the perfusion term. A correction coeffi cient that is close to zero implies a signifi cant countercurrent rewarming of the paired vein and a coeffi cient of unity implies no rewarming.…”
Section: Limitationsmentioning
confidence: 99%
“…The EF-approach in essence corrects the Pennes-term by an EF-function …0 µ EF µ 1 †, dependent on perfusion ! and the local coordinate of tissue depth z (mean value in muscle 0.72 18 ). With this approach, a substantial correction of the perfusion term takes place in the peripheral part of the muscles and in the whole tissue where low perfusion rates are present…”
Section: Heat Transfer In Capillariesmentioning
confidence: 99%
“…In a whole limb simulation, however, it is impossible to take into account every single vessel, so many attempts have been made to develop models of substitutional processes which adequately describe the thermal eOE ect of perfusion. [15][16][17][18][19][20][21][22] A special form of hyperthermia treatment is the hyperthermic isolated extremity perfusion (® gure 1). [23][24][25][26][27][28] The extremity circulation is separated from the body circulation and perfused extracorporally by a heart-lung-machine.…”
Section: Introductionmentioning
confidence: 99%